Anion‐Doped Cobalt Selenide with Porous Architecture for High‐Rate and Flexible Lithium–Sulfur Batteries. Issue 9 (15th August 2021) - Feng, Tao; Zhao, Teng; Zhu, Shuangfei; Zhang, Nanxiang; Wei, Zhuangzhuang; Wang, Ke; Li, Li; Wu, Feng; Chen, Renjie
Abstract: Emerging catalytic host for sulfur is an effective approach to breaking the limits of lithium–sulfur batteries for practical applications. Herein, the hydrangea‐shaped Co0.85 Se electrocatalyst with macroporous architecture is synthesized. Besides, to improve the electronic conductivity of Co0.85 Se, some defects (S‐doped) are introduced into the structure of crystals. The S‐doped Co0.85 Se exhibited an outstanding electrocatalytic effect on lithium polysulfides conversion and can induce and regulate uniform growth of insoluble Li2 S on its surface due to the synergistic adsorption by Se and S. As a result, the S/C cathode achieved a high initial capacity of 1340.6 mAh g −1 at 0.5 C and a stable cycling capacity of 666.6 mAh g −1 at 1 C after 500 cycles by 5 wt% Co0.85 SeS additions. Moreover, high S loading cathodes are designed through in situ synthesis of Co0.85 SeS on flexible carbon cloth (Co0.85 SeS@CC). The porous and open framework of Co0.85 SeS@CC facilitated electrolyte infiltration and accommodated the volume change of sulfur during the charge/discharge process. Taking by these advantages, a high areal capacity of 9.663 mAh cm −2 is achieved at a high sulfur loading of 9.98 mg cm −2 . Even at a high current density of 15 mA cm −2, a reversible capacity of 603.7 mAh g −1 is maintained at a sulfur loading of 6.52 mg cm −2 . This proposed work provides a feasible approach to high‐rate and flexible Li–S batteries. Abstract : A highly conductive S‐doped catalytic host (Co0.85 SeS) is designed for lithium–sulfur batteries. It exhibits an outstanding electrocatalytic effect on lithium polysulfides (LiPSs) conversion by integrating experimental data and DFT calculations. Furthermore, high S loading cathodes are prepared through in situ synthesis of the Co0.85 SeS on flexible carbon cloth (Co0.85 SeS@CC). Pouch batteries based on cathodes show potential application in flexible electronic devices.